Selection of Nonlethal Early Biomarkers to Predict Gilthead Seabream (Sparus aurata) Growth - Rafael Angelakopoulos; Andreas Tsipourlianos; Katerina A. Moutou; Alexia E. Fytsili; Anthi Tsingene; Eleni Galliopoulou; Leonidas Papaharisis; Zissis Mamuris; Themistoklis Giannoulis; Arkadios Dimitroglou (Aquaculture Nutrition)
One of the main challenges in aquaculture is the constant search for sustainable alternative feed ingredients that can successfully replace fishmeal (FM) without any negative effects on fish growth and health. The goal of the present study was to develop a toolbox for rapidly anticipating the dynamics of fish growth following the introduction of a new feed; nonlethal, biochemical, and molecular markers that provide insights into physiological changes in the fish. A nutritional challenge by feeding a conventional feed rich in FM protein (FM diet) versus an experimental feed rich in plant protein (PP) and low FM inclusion (PP diet), in 20 different families of gilthead sea bream (Sparus aurata) was performed. Fifteen and 30 days after the initiation of the nutritional challenge, the transcriptional response of gilthead seabream erythrocytes along with classical hematological biochemical markers were compared. Zootechnical, biochemical, and transcriptome data from each family under different dietary treatments were combined into a classification model to identify variables that can predict the growth rate at the end of the 14-month farming period (July 2018–September 2019). A highly accurate model was produced (A > 80%) based on the combination of seven markers (five molecular and two biochemical markers) and with high potential in separating faster and slower growing fish as early as 30 days after the initiation of feeding.